(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Organic food may become more popular as a result of the ongoing shift in consumer attitudes towards organic products; for this reason, it is crucial to research consumer repeat purchase behavior for organic food in emerging nations like India. The repeat purchase habits of consumers in Delhi NCR areas were examined in this study. This study’s sample consisted of people who were already customers and had made many purchases, in contrast to earlier research that primarily used random individuals. More precisely, by adding environmental concern and trust variables to the extended Theory of Planned Behavior model, this discrepancy was investigated for repeated purchases. An offline survey was utilized to gather data from 446 customers, and structural equation modeling was employed to analyze the result. This work primarily validates the usefulness of the extended model, and it shows that the model’s predictive ability is higher than that of the basic model. Furthermore, trust and environmental concern have a positive effect on repeat purchases of organic food products. In conclusion, the relationship between trust, environmental concern, and the extended theory of planned behavior towards repeated purchases of organic food is mediated by purchase intention and actual buying behavior.